2017
DOI: 10.19044/esj.2017.v13n27p279
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric in Patient Profile at the Department of Internal Medicine at Niamey National Hospital, Niger

Abstract: Abstract:Background: The ageing population in developing countries has brought a demographic and an epidemiological transition, with the impact of chronic diseases resulting from life style changes on the health status of the population. Objective: To describ a profile geriatrics patient, specifically to identify epidemiologic, clinical, etiologic and outcome of this group at the department of internal medicine to NNH Patients and method: Medical records of all geriatric patients aged ≥65 years admitted at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…Old age people in the community were more susceptible to malnutrition when using MNA compared to hospitals and longterm care centers. The prevalence ranged from 5.7% in Niger (Andia et al, 2019) to 56% in Egypt (Esmayel et al, 2013) and 18% in Egypt (Esmayel et al, 2013) to 58.5% in Niger (Andia et al, 2019), respectively. While 2.24% (Adebusoye et al, 2018) to 40.46% (Abd-el-gawad et al, 2014) and 11.8% (Adebusoye et al, 2012) to 52.7% (Abd-el-gawad et al, 2014) of old age people all from the Nigerian hospitals were malnourished and at risk of malnutrition, respectively.…”
Section: Prevalence Of Malnutrition Using Mnamentioning
confidence: 99%
See 1 more Smart Citation
“…Old age people in the community were more susceptible to malnutrition when using MNA compared to hospitals and longterm care centers. The prevalence ranged from 5.7% in Niger (Andia et al, 2019) to 56% in Egypt (Esmayel et al, 2013) and 18% in Egypt (Esmayel et al, 2013) to 58.5% in Niger (Andia et al, 2019), respectively. While 2.24% (Adebusoye et al, 2018) to 40.46% (Abd-el-gawad et al, 2014) and 11.8% (Adebusoye et al, 2012) to 52.7% (Abd-el-gawad et al, 2014) of old age people all from the Nigerian hospitals were malnourished and at risk of malnutrition, respectively.…”
Section: Prevalence Of Malnutrition Using Mnamentioning
confidence: 99%
“…Based on the quality assessment checklist, studies were either in moderate (6-8 points) (Ijarotimi and Keshinro, 2008;Khater and Abouelezz, 2011;Mahfouz et al, 2013;Abd-el-gawad et al, 2014;Alao et al, 2015;OC et al, 2015;El-desouky and Abed, 2017;Adebusoye et al, 2018;Adebusoye et al, 2019;Andia et al, 2019;Faten et al, 2019;Allah et al, 2020) or high-quality groups (9 or 10 points) (Nyaruhucha et al, 2001;Olasunbo and Olubode, 2006;Marais et al, 2007;Adebusoye et al, 2012;Cheserek et al, 2012;Andre et al, 2013;Esmayel et al, 2013;Mkhize et al, 2013;Rouvray et al, 2014;Tessfamichael et al, 2014;Aganiba et al, 2015;Naidoo et al, 2015;Pilleron et al, 2015;El-sherbiny et al, 2016;Hailemariam et al, 2016;Robb et al, 2017;Agbozo et al, 2018;Diendéré et al, 2018;Abdu et al, 2019;Adhana et al, 2019;Apprey et al, 2019;Legesse et al, 2019;Abate et al, 2020). Study bias was mostly exacerbated as a result of convenience sampling and a low response rate among study participants.…”
Section: Quality Of the Studiesmentioning
confidence: 99%
“…This suggests that metabolic changes are a universal feature of aging. Loss of strength, functional decline, and poor endurance may make this more obvious [12].…”
Section: Open Access Journal Of Gerontology and Geriatric Medicinementioning
confidence: 99%
“…Several studies have shown the prevalence of 24% malnutrition and 46% malnutrition risk in community and hospitalized older adults [12]. In 2021, Olawumi et al, found a 25.3% of malnutrition and over 56.6% at risk of malnutrition among older population in northwest, Nigeria.…”
Section: Open Access Journal Of Gerontology and Geriatric Medicinementioning
confidence: 99%
“…Stroke is the second leading cause of death in developing countries, behind cardiovascular disease [1]. In West Africa, the hospital frequency about stroke in young seniors was 18% in Niamey, 30% in Dakar, 29% in Ouagadougou and 28.5% in Gabon [2,3,4,5]. Literature about very elderly stroke is not frequent in sub-Saharan Africa while there is even the problem of early management in a neurovascular unit which undoubtedly improves the prognosis at all ages.…”
Section: Introductionmentioning
confidence: 99%